FUEL SUBSIDY REMOVAL AND THE UBIQUITY OF HARDSHIP IN NIGERIA: PRESIDENT BUHARI AND LESSONS FROM KING REHOBOAM - Bassey Obo, Ugumanimn; Iba Omenka, Jacob; Venenge Agishi, Tabitha; Coker, Maurice Ayodele (Advances in Social Sciences Research Journal, 2017)
Abstract This essay specifically focuses attention on one of the policies of the government of Muhammadu Buhari, that is, the policy of removal of fuel subsidy and the increase of pump price of petrol in Nigeria, and the dire consequences it has had for the wellbeing of the people. It is argued that given the size of the pump price increase, the way it was enforced, and the enormous increases in the costs of goods and services which it has engendered, President Buhari appears to be in the same league with the Biblical King Rehoboam who presided over an era of unprecedented cruelty in Israel. It is also reasoned that if well-articulated, managed and targeted, subsidy can serve as a policy instrument for the promotion of the public good. This paper also stresses the need for Nigeria to urgently stop the importation of refined petroleum products and begin to refine its products domestically. dire consequences